Midline one-stage complete unifocalization early outcomes from a single center - Oktay Korun; Okan Yurdakök; Mehmet Dedemoğlu; İlker Kemal Yücel; Ahmet Çelebi; Şefika Türkan Kudsioğlu; Ahmet Sasmazel; Numan Ali Aydemir (Anatolian Journal of Cardiology)
Objective: This study aims to present our experience with single-stage complete unifocalization and intraoperative flow study for the repair of ventricular septal defect, pulmonary atresia, and major aortopulmonary collateral arteries. Methods: This study was conducted through retrospective chart review of all the patients who underwent complete single-stage midline unifocalization in a single tertiary-care institution. Results: Twenty-two patients underwent midline single-stage unifocalization. The median age was 11 months (IQR: 5–21 months). The number of collateral arteries unifocalized was between one and three (median two). In-hospital mortality was 5%. Follow-up was complete; and the median follow-up regarding survival was 20 months (IQR: 10–28 months). There were three late deaths, and the estimated survival rate was 80% at 10 months and on. Out of 22 patients, ventricular septal defect was closed in the first surgery in three patients (14%) and the second surgery in four patients (19%). Total seven patients underwent surgical total repair (32%). Additionally, one out of four patients whose ventricular septal defects were closed with a fenestrated patch is under follow-up with a small ventricular septal defect, while two are waiting for ventricular septal defect closure. Therefore, total eight patients (36%) have reached total correction. Conclusion: Single-stage unifocalization is a feasible treatment option in ventricular septal defect, pulmonary atresia, and major aortopulmonary collateral arteries. This cohort had unfavorable results regarding the rate of complete repair. The pitfalls encountered were related to problems with meticulous surgical technique, complete unifocalization, and correct implementation of the flow study.